Talk or Text? Evaluating Response Rates by Remote Survey Method during Covid-19 - Sofia Amaral; Lelys Dinarte-Diaz; Patricio Dominguez; Steffanny Romero; Santiago M. Perez-Vincent (Center for Economic Studies and ifo Institute (CESifo), 2022)
Researchers and policy makers face significant challenges in selecting a method to conduct remote surveys, especially when collecting sensitive information or during turbulent life stages of hard-to-reach groups. In the context of the COVID-19 lockdown, we randomly selected about 600 adults in El Salvador to survey using two different tools: telephone interviews or a self-completion survey via WhatsApp. We find that phone-based surveys increase the rate of survey completion by 42 percentage points. We document even larger effects for women and older adults. Although direct costs of phone-based surveys are substantially larger—doubling implementation cost—our estimates imply that when adjusted for the probability of completion, the costs of conducting phone-based surveys can be 25 percent lower.
Keywords: C83; C81; C93; D91; 330; phone surveys; WhatsApp surveys; response rate; survey experiments